KETIDAKPUASAN KERJA PEKERJA WANITA INDUSTRI KERAJINAN TANGAN TENUN SONGKET PEKANBARU RIAU - Mita Rosaliza; Lanang Diayudha (Universitas Bunda Mulia, 2017)
Workers as human resouce contribute significantly to productivity in an organization. Their contribution is big even when technology has replaced some of their rules and functions. However, workers are not free from facing problems at the work place related to the work that they do, the work place itself, other wokers etc. Research conducted at a Songket handicraft industry X is to identify sources of dissatisfaction face by their workers at the work place. The study also intends to see how the workers express their feelings of dissatisfaction and to understand workers attitude towards their place of work. This is an empirical study using questionnaire and interview as tha main techniques in a survey for gathering data. A total of 20 respondents were met. The SPSS program was used to analyze the quantitative data. The fundings show that the main cause of dissatisfaction among the workers is the wages they receive. Other extrinsic (such as management style, work burden and depression from other workers)) and intrinsic factors (such as appreciation and respect) also contribute to the dissatisfaction among workers. Besides that, problem at work place continues because the workers are not concern about their right and welfare. As such it can be said that workers need to be managed well and their well being looked after. Otherwise, it could be a cause of dissatisfaction among the workers and without proper channels to help address it could lead the workers to express them in the informal and negative ways.Key words : human resource, songket, handy craft